Representation of breastfeeding in cinema - Visa Barbosa, Mariona (Estudios sobre el Mensaje Periodístico, 2017)
This paper analizes brestfeeding representations in 20 films, since 1973 until today, to see how breastfeeding is shown in the cinema and what connotations receives. The methodology used is based on a qualitative content analysis of discourse and visual information of the films, as well as of a 150 people survey about breastfeeding representation in the media. The findings confirm the starting hypothesis, highlighting how breastfeeding is under represented in film production, and linked to erotic and humorous situations. It also contributes to spread false myths and represent as an abnormality the breastfeeding of children over one year old.